2014
DOI: 10.11648/j.earth.20140305.12
|View full text |Cite
|
Sign up to set email alerts
|

Gutenberg-Richter Law Parameters Analysis Using the Hellenic Unified Seismic Network Data Through FastBee Technique

Abstract: Abstract:The mapping of the minimum completeness magnitude Mc and parameters (a-and b-value) of the Guttenberg-Richter (G-R) law was studied for Greece territory and adjacent areas by using the new earthquakes catalog produced by the Hellenic Unified Seismological Network (HUSN). For the calculation of the parameters a-and b-values the visual method of the completeness magnitude (Mc) definition was used by means of FastBee technique. The results show that with the commissioning of the new network HUSN, the Mc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
4
0
4
Order By: Relevance
“…Here, the constant "b" is slope parameter with 0.89 value which indicates this slope is slightly gentler i.e. more productive for the larger aftershock and lies in the expected range of 0.5 to 1.5 globally [10,11].…”
Section: Gutenberg-richter Law For Aftershock Data 2015mentioning
confidence: 94%
See 1 more Smart Citation
“…Here, the constant "b" is slope parameter with 0.89 value which indicates this slope is slightly gentler i.e. more productive for the larger aftershock and lies in the expected range of 0.5 to 1.5 globally [10,11].…”
Section: Gutenberg-richter Law For Aftershock Data 2015mentioning
confidence: 94%
“…The exponential pattern of relationship between frequency and magnitude is observed. The frequency magnitude distribution reflects fundamental properties of how earthquakes grow and stop [11]. The Gutenberg Richter parameters were calculates, by Least Square Method for aftershock data 2015, using the relation as Log10 N (m) = ab M = 6.5 -0.89 M. This Gutenberg-Richter relation expresses the relationship between the magnitude and total number of earthquakes in any given region (Nepal) and time period of at least that magnitude (≥ 4).…”
Section: Gutenberg-richter Law For Aftershock Data 2015mentioning
confidence: 99%
“…Penelitian ini melibatkan tiga variabel diantaranya variabel bebas adalah besaran momen ( ), variabel kontrol adalah distribusi parameter a-value dan bvalue menurut persamaan Gutenberg-Richter di Nusa Tenggara Timur, serta variabel respon adalah frekuensi kejadian gempa bumi, a-value, b-value, dan dimensi fraktal. Data gempa bumi dan visualisasi waktu kejadian dapat menjadi parameter seismik dengan bantuan software untuk pemetaan (Popandopoulos G. A. & Chatziioannou E., 2014).…”
Section: Metode Penelitian Studi Literatur Dan Pengolahan Dataunclassified
“…( ) (8) N merupakan frekuensi kejadian gempa bumi, a merupakan konstanta keaktifan seismik, b merupakan konstanta kerapuhan batuan dan M merupakan magnitudo gempa bumi. Pada persamaan 8 menunjukkan persamaan linear, log N adalah variabel respon sumbu Y dan M, variabel bebas sumbu X. Persamaan a-value yaitu perpotongan sumbu Y di sumbu X yang menunjukkan jumlah data gempa dengan luas wilayah, sedangkan b-value yaitu gradien suatu garis hubungan regresi yang menunjukkan hubungan antara jumlah gempa besar maupun gempa kecil (Popandopoulos G. A. & Chatziioannou E., 2014).…”
Section: Metode Maximum Likelihoodunclassified
“…In seismicity studies, some parameters have a particularly important role. Among others, these are the maximum magnitude (recorded, possible, expected), the b-value of the Gutenberg-Richter (GR) frequency-magnitude (FMD) relation, and a parameter related to the seismic activity (mean seismic activity rate or the a-value of GR) [1][2][3][4][5][6][7][8][9][10][11][12][13]. Some of these studies are based on seismic zonations [1,2], and others are found in a purely geographical grid division [7,11,14,15].…”
Section: Introductionmentioning
confidence: 99%